2004
DOI: 10.1111/j.1468-2982.2004.00762.x
|View full text |Cite
|
Sign up to set email alerts
|

A Double-Blind Study of SB-220453 (Tonerbasat) in the Glyceryltrinitrate (GTN) Model of Migraine

Abstract: The need for experimental migraine models increases as therapeutic options widen. In the present study, we investigated SB-220453 for efficacy in the glyceryltrinitrate (GTN) human experimental migraine model. SB-220453 is a novel benzopyran compound, which in animal models inhibits neurogenic inflammation, blocks propagation of spreading depression and inhibits trigeminal nerve ganglion stimulation-induced carotid vasodilatation. We included 15 patients with migraine without aura in a randomized double-blind … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2008
2008
2010
2010

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 15 publications
2
28
0
Order By: Relevance
“…A new approach for this problem is to study drugs reducing trigeminal nerve stimulation, like tonabersat, a gap-junction blocker of the trigeminal nerve that does not exert vasoconstrictive properties [13].…”
Section: Preventive Treatmentmentioning
confidence: 99%
“…A new approach for this problem is to study drugs reducing trigeminal nerve stimulation, like tonabersat, a gap-junction blocker of the trigeminal nerve that does not exert vasoconstrictive properties [13].…”
Section: Preventive Treatmentmentioning
confidence: 99%
“…A trial investigated the efficacy of SB-220453 in the glyceryltrinitrate (GTN) human experimental migraine model [11]. The study reported, ''15 patients with migraine without aura entered a randomized, double-blind, crossover study with 40 mg or placebo followed by a 20-min GTN infusion.…”
Section: Gap Junction Blocker (Preventive)mentioning
confidence: 99%
“…Cortical spreading depression (CSD) is a neurophysiologic phenomenon that since its discovery by Leão, has been amply investigated and is now widely recognized as the neurophysiologic substrate of migraine aura [1]. SB-220453 (now known as tonabersat) is a benzoylamino-benzopyran compound that has shown the ability to inhibit CSD in animal models of migraine [2]. Great interest has developed with regard to the possibility that pharmacologic CSD inhibition may prevent migraine headache attacks, although in a human model of migraine, tonabersat failed as a preemptive antimigraine agent in a double-blind study [2].…”
Section: Introductionmentioning
confidence: 99%
“…SB-220453 (now known as tonabersat) is a benzoylamino-benzopyran compound that has shown the ability to inhibit CSD in animal models of migraine [2]. Great interest has developed with regard to the possibility that pharmacologic CSD inhibition may prevent migraine headache attacks, although in a human model of migraine, tonabersat failed as a preemptive antimigraine agent in a double-blind study [2]. For prophylaxis, however, commonly prescribed migraine preventatives such as topiramate, valproate, propranolol, and amitriptyline all were recently found to inhibit CSD in a dose-dependent fashion when administered chronically and on a daily basis in rats, suggesting that CSD can provide a common therapeutic target for migraine prophylactic drugs [3].…”
Section: Introductionmentioning
confidence: 99%